The 2012–2016 eruptive cycle at Copahue volcano (Argentina) versus the peripheral gas manifestations: hints from the chemical and isotopic features of fumarolic fluids - Tassi, F. (2017)
This study presents the chemical and isotopic compositions of hydrothermal gases from fumaroles discharging around Copahue volcano (Argentina). Gas samples, including those from two fumaroles at the active summit crater, were collected during 13 surveys carried out by different research teams from 1976 to February 2016. The time-series of H2, CO and light hydrocarbons showed episodic increases related to the main events of the last eruptive cycle that started on 19 July 2012. Concentration peaks were likely caused by enhanced input of hot magmatic fluids affecting the hydrothermal reservoir. These data contrast with the temporal variations shown by Rc/Ra and δ13C-CO2 values in 2012–2014, which indicated an increasing input from a crustal fluid source. In 2015–2016, however, these isotopic parameters showed opposite trends; their composition became closer to that of the two summit fumaroles, which possibly corresponds to that of the deep magmatic-related end-member. The delayed and reduced compositional changes in the peripheral hydrothermal fluid discharge in response to the 2012–2016 eruptive events suggest that geochemical surveys of these emissions are unlikely to provide premonitory signals of volcanic unrest if the volcanic activity remains centered in the main crater. Instead, an instrument which is able to provide measurements of volcanic gases in the air (e.g. MultiGAS) may be used to detect changes at the summit crater. Otherwise, monitoring of seismic activity and ground deformation, as well as the periodic measurement of the chemistry of the water in the Rio Agrio, which is fed by thermal discharge from the summit crater, seem to represent the most reliable means of monitoring at Copahue. However, the relative compositional stability of the hydrothermal reservoir is a great advantage in terms of geothermal resource exploitation and could encourage new investments in the Copahue geothermal project which was abandoned in the 1990s.